Motyw nadziei w najnowszej poezji Dmitrija Strocewa - Osiewicz, Bartosz (Studia Rossica Posnaniensia, 2023)
This article is devoted to the analysis of the motif of hope in the latest poetry of the Belarusian independent poet Dmitry Strotsev. The peaceful Belarusian revolution of 2020 became a source of inspiration for Strotsev and influenced the form and content of his latest works. The methodological basis of the research is focused on the observations on hope made by the French philosopher Gabriel Honoré Marcel in the essay Outline of the phenomenology and metaphysics of hope (1942), and by the priest Józef Tischner in the essay Binding of Hope (1973). In Strotsev’s latest poetry, the theme of hope is combined with the heroic peaceful struggle for freedom undertaken by Belarusian society and is inscribed in an intertextual dialogue with the Bible. The poet presents a collective portrait of people filled with hope, which is an impulse for them to act. It shows society at the time of a test of enslavement. The answer to enslavement is opposition born of hope. The experience of heroism also flows from hope. Strotsev’s works not only immortalize the people who fought for freedom, but also multiply the hope inherent in all those who take up a heroic fight against evil. Hope allows them to visualize the “fragility” and “impermanence” of evil. It is also a comfort to those who are suffering from loss. It also helps not to succumb to despair.